2020
DOI: 10.1093/ndt/gfaa140.mo039
|View full text |Cite
|
Sign up to set email alerts
|

Mo039the 24-Week Interim Analysis Results of a Randomized, Double-Blind, Placebo-Controlled Phase Ii Study of Atacicept in Patients With Iga Nephropathy and Persistent Proteinuria

Abstract: Background and Aims IgA nephropathy (IgAN) is the most common primary glomerulonephritis in the world. Despite being described over 50 years ago, there remains no approved therapy for this common global cause of kidney failure. The central pathogenic feature in IgAN is the formation of circulating IgA containing immune complexes which have the propensity to deposit in the kidneys and trigger glomerular inflammation and tubulointerstitial scarring. The primary substrate for immune complex form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…These other agents were a recombinant soluble TACI-Fc (sTACI-Fc) decoy receptor that binds APRIL and BAFF at 6.4 nM and 160 pM respectively (Wu et al, 2000), as well as an antibody against BAFF ( α BAFF Ab) with a K D of 0.995 nM and no reported binding to APRIL (Shin et al, 2018). The clinical versions of both molecules are currently used for the treatment of various B cell related autoimmune diseases (Bag-Ozbek and Hui-Yuen, 2021; Barratt et al, 2020; Lee and Amengual, 2020). We performed an in vivo head-to-head comparison study evaluating the antitumor efficacy of sBCMA-Fc V3, sTACI-Fc, α BAFF Ab and wild-type sBCMA-Fc in SU-DHL-6 DLBCL tumors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These other agents were a recombinant soluble TACI-Fc (sTACI-Fc) decoy receptor that binds APRIL and BAFF at 6.4 nM and 160 pM respectively (Wu et al, 2000), as well as an antibody against BAFF ( α BAFF Ab) with a K D of 0.995 nM and no reported binding to APRIL (Shin et al, 2018). The clinical versions of both molecules are currently used for the treatment of various B cell related autoimmune diseases (Bag-Ozbek and Hui-Yuen, 2021; Barratt et al, 2020; Lee and Amengual, 2020). We performed an in vivo head-to-head comparison study evaluating the antitumor efficacy of sBCMA-Fc V3, sTACI-Fc, α BAFF Ab and wild-type sBCMA-Fc in SU-DHL-6 DLBCL tumors.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, inhibition of TACI signaling (e.g. atacicept) showed modest efficacy in MM but is clinically effective at treating other B-cell related diseases such as IgA Nephropathy (24).…”
Section: Introductionmentioning
confidence: 99%
“…Atacicept (NCT02808429 and NCT04716231) and RC-18 (NCT04291781) are recombinant human BLyS receptor-antibody fusion proteins that target both BAFF and APRIL, and phase II clinical trials to evaluate their efficacy and safety in the treatment of IgAN are currently ongoing ( Table 1 ). Notably, the preliminary results of a phase II study (NCT02808429) examining the safety and efficacy of atacicept in reducing Gd-IgA1 and renal activity in patients with IgAN were previously presented by Barratt et al recently ( Barratt et al, 2020 ). The interim analysis revealed that, at week 24, patients with IgAN had a consistent, dose-dependent reduction in IgA, IgG, IgM, and Gd-IgA1, and a higher median % reduction from baseline in UPCR with atacicept than did those who received placebo.…”
Section: Regulation Of Immune Response In Iganmentioning
confidence: 99%
“…Atacicept is a fully humanized fusion protein that contains the extracellular portion of TACI and inhibits both BAFF and APRIL signaling. Preliminary results from a Phase II trial suggest a dose-dependent effect on proteinuria levels [ 36 ]. This trial was terminated early due to slow recruitment, and further studies of atacicept in IgAN are planned.…”
Section: Targeting B Cellsmentioning
confidence: 99%